2016
DOI: 10.1088/0963-0252/25/4/045001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Monte Carlo methods for plasma-surface reactions

Abstract: Different dynamical Monte Carlo algorithms to investigate molecule formation on surfaces are developed, evaluated and compared with the deterministic approach based on reaction-rate equations. These include a null event algorithm, the n-fold way / BKL algorithm and an "hybrid" variant of the latter. NO 2 formation by NO oxidation on Pyrex and O recombination on silica with the formation of O 2 are taken as case studies. It is shown that dynamical Monte Carlo schemes are flexible, simple to implement, describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
95
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(101 citation statements)
references
References 71 publications
5
95
1
Order By: Relevance
“…In the first approximation in case of a square grid, the correction factor is equal to 3/4 which corresponds to the probability of 1/4 for an atom to return to its initial position after two successive hops. This effect is called back diffusion and it can be shown that it is important for processes that have elementary probabilities close to one, such as the occupation of empty chemisorption sites by diffusion (R5), but it should be neglected for processes with a low elementary probability, such as L‐H recombination (R6), (R7) …”
Section: Model Formulationmentioning
confidence: 99%
See 4 more Smart Citations
“…In the first approximation in case of a square grid, the correction factor is equal to 3/4 which corresponds to the probability of 1/4 for an atom to return to its initial position after two successive hops. This effect is called back diffusion and it can be shown that it is important for processes that have elementary probabilities close to one, such as the occupation of empty chemisorption sites by diffusion (R5), but it should be neglected for processes with a low elementary probability, such as L‐H recombination (R6), (R7) …”
Section: Model Formulationmentioning
confidence: 99%
“…The elementary probability PnormalRLH can be calculated in the same way as P R with the appropriate values of the energy barrier and the pre‐exponential factor. In Guerra et al it is assumed that upon an encounter between two physisorbed atoms the recombination occurs with probability 1. This assumption can be justified by the fact that physisorbed atoms interact only weakly with the surface and hence reaction (R7) is similar to a 3‐body gas phase recombination which proceeds with no barrier for many atomic species .…”
Section: Model Formulationmentioning
confidence: 99%
See 3 more Smart Citations